An International Continence Society (ICS) report on the terminology for single‐use body worn absorbent incontinence products. Issue 8 (11th September 2020) - Fader, Mandy; Cottenden, Alan; Chatterton, Chris; Engqvist, Helena; Eustice, Sharon; Newman, Diane K.; Ostaszkiewicz, Joan; Palmer, Mary H.; Willson, Tara; Haylen, Bernard
Abstract: Aims: In 2016, the International Continence Society (ICS) Standardization Steering Committee appointed a working group to address the confusing plethora of synonyms currently used to describe single‐use body worn absorbent incontinence products by recommending preferred terminology. Methods: An online questionnaire was posted in 2016/17 inviting input from stakeholders internationally. The data were analyzed and conclusions progressively refined through working group discussions, an open meeting at the 2017 annual ICS conference, and a review of further iterations—including from the parent ICS Standardization Committee—until consensus was reached. Partway in, the International Organization for Standardization started a project with similar scope and the two organizations liaised to harmonize their conclusions while respecting each other's processes. Results: A hundred people from 18 countries responded to the questionnaire. About a third (32.2%) of those declaring their nationality were from the UK and a further third (34.5%) from other English‐speaking countries. Two‐thirds (67.8%) lived in Europe; around a quarter (23%) in North America; and 9.2% in Australasia. Seven main design categories of products were identified and, while clear consensus was readily achieved in naming some of them, others required more work to determine the best term among multiple contenders. Conclusions: The working group concluded that the seven product design categories should be called: (a) pads; (b) unbacked pads; (c) male pads; (d) male pouches; (e) pull‐on pads (protective underwear); (f) all‐in‐ones (wrap‐around pads, adult briefs); and (g) belted pads (belted products), in which the bracketed terms are judged acceptable (though not preferred) alternatives.